Analysis of Educational Values in Malay Zapin Dance - Azzahra Nurul Nadilah; Anzela Ravika; Ayu Apriana; Maryamah Maryamah (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2023)
Research was conducted on one of the arts and cultures in Indonesia, namely dance. The dance chosen as the object of this research is the Malay Zapin Dance. This research was conducted to discover what Islamic values are contained in dance, which is used as one of the arts. The study was performed using the Literature Review Method. Researchers conducted research by collecting various sources that conducted similar research and reviewing the research results by providing updates on the values of Islamic education, which will be used as a reference for subsequent analysis. The research results show several Islamic educational values found in the Malay Zapin dance, including Worship, Aqidah, and Moral Values found in several Malay Zapin Tatri movements. This can be used as a reference to become a source of knowledge regarding the values of Islamic education.